Aortic dilatation using cardiac magnetic resonance in asymptomatic ELITE athletes. (11th May 2022) - Verwijs, SM; Van Hattum, JC; Stomilovic, N; Daems, JJN; Boekholdt, SM; Planken, RN; Groenink, M; Van Randen, A; Bakermans, AJ; Nederveen, AJ; Moen, MH; Pinto, YM; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Purpose: Aortic dilatation is associated with acute aortic pathology. Cardiac magnetic resonance (CMR) data in asymptomatic elite athletes is lacking. Therefore, we investigated the prevalence of aortic dilatation in a cohort of elite-level athletes using CMR. Methods: We performed a cross-sectional study of aortic dimensions among elite-level (national-, international-, Olympic-, Paralympic-level or comparable) athletes. All athletes were asymptomatic and examined during pre-participation screening. Each underwent CMR with 3D whole heart in diastole (1.5 mm voxel) for aortic measurements, next to cine imaging, late gadolinium enhancement (LGE), and T1-mapping. We defined dilatation as 38 and 40 mm at the aortic root (sinus of Valsalva cusp-cusp), 27 and 31 mm at the sinotubular junction, and 23 and 26 mm at the level of the diaphragm, in male- and female athletes, respectively. Athletes were grouped for having 0- (normal), 1-, 2- or 3 measurements above cut-off values. Results: We screened 156 athletes, 41% female, with a mean age (±SD) of 28±7 and body surface area (BSA) of 2.0±0.2 m2. Mean aortic dimensions were 33±4 mm for the sinus of Valsalva, 28±3 mm for the sinotubular junction, 20±3 mm for the aorta at diaphragm. We observed indexed end-diastolic volumes (EDVi) of 122±20 and 123±20 ml/m2, indexed end-systolic volumes (ESVi) of 53±13 and 54±16 ml/m2, stroke volumes (SV) of 129±36 and 126±39 ml, and ejection fractions (EF) of 56±5 and 55±6 %, in the left- (LV) and right ventricle (RV), respectively Fifty-three (34%) athletes, of which 45% female, had 1 or 2 aortic measurements above conventional cut-off values (Table 1). Eleven (7%), 18% female, had 2 aortic measurements above cut-off values. No athlete had all 3 measurements above cut-offs values. Athletes with 2 dilated measurements compared to athletes with 1 or 0 dilated measurements, had greater LV EDVi (145±19 vs. 119±18 vs. 120±19 ml/m2, p<0.001), greater RV EDVi (142±18 vs. 119±17 vs. and 122±20 ml/m2, p=0.002), greater LV ESVi (66±10 vs. 51±13 vs. 52±13 ml/m2, p=0.002), greater RV ESVi (66±10 vs. 53±13 vs. 53±17 ml/m2, p=0.039), greater LV SV (156±26 vs. 132±35 vs. 125±36 ml, p=0.020), and greater RV SV (152±25 vs. 130±34 vs. 121±41 ml, p=0.031), 2- vs, 1- vs. 0 dilated segments, respectively (Table 1, Figure 1). Athletes with dilated measurements had no LGE (excluding the hinge point), no difference in T1-mapping times, or LV- and RV EF, compared to athletes without dilated measurements. Conclusion: One in three elite-athletes has dilatation in one or more aortic segments, including the sinus of Valsalva, sinotubular junction, or the aorta at diaphragm. Athletes with 2 dilated measurements (7%) had greater LV- and RV EDVi, ESVi, and SV, suggesting an association with ventricular volumes. Our findings in asymptomatic elite athletes, with normal EF and no LGE and comparable T1-mapping times, could be a sign of an outspoken physiological sports adaptation, instead of pathology.